The potential of SiK® fertilization in the resilience of chestnut plants to drought - a biochemical study - Carneiro-Carvalho, Andreia; Pinto, Teresa; Gomes-Laranjo, José; Anjos, Rosário (Frontiers in Plant Science, 2023)
Silicon is an essential mineral nutrient, that plays a crucial role in the metabolic, biochemical, and functional mechanisms of many crops under environmental stress. In the current study, we evaluated the effect of SiK® fertilization on the biochemical defense response in plants exposed to water stress. Castanea sativa plants were fertilized with different concentrations of potassium silicate (0, 5, 7.5, and 10 mM of SiK®) and exposed to a non-irrigation phase and an irrigation phase. The results indicate that silicon promoted the synthesis of soluble proteins and decreased the proline content and the oxidative stress (reduced electrolyte leakage, lipid peroxidation, and hydrogen peroxide accumulation) in tissues, due to an increase in ascorbate peroxidase, catalase, and peroxidase activity, which was accompanied by the rise in total phenol compounds and the number of thiols under drought conditions. This study suggests that exogenous Si applications have a protective role in chestnut plants under water deficit by increasing their resilience to this abiotic stress